TINDAK PIDANA EKSPLOITASI ANAK UNTUK KEPENTINGAN EKONOMI (Studi Kasus Putusan No.1608/PID.Sus/2016/PN.Tng) - Vita Irawan Sari (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
Child exploitation is arbitrary action and discriminatory treatment against children by the community or their own families with the aim of forcing the child to do something without regard to children's rights, for example cases of child exploitation by Tajudin who employ children as mortar sellers on the street. general by placing the child on the side of the highway by hoping that someone feels sorry for him to be given money. In this case, the issue raised is whether the act of the defendant in decision number: 1608 / Pid.Sus / 2016 / PN.Tng is a criminal act of child exploitation and whether the judge's consideration in deciding to release the case of child exploitation is in accordance with the statutory regulations. applicable. This research is a descriptive analysis so that the data obtained are analyzed qualitatively. The theoretical basis refers to article 1 number 7 of the Republic of Indonesia Law number 21 of 2007 concerning the crime of combating trafficking in persons. The results of the research conducted by the author in this case is that the exploitation of children is a criminal act, this is clearly stated in article 1 number 7 of the Republic of Indonesia Law number 21 of 2007 concerning the eradication of the crime of trafficking in persons. The judge stated that the defendant's actions were proven but the act did not constitute a criminal act and the judge released the defendant from all legal charges. In this case the act committed by the defendant had been approved by both parents to sell mortar, therefore the elements contained in the article were not a crime.